Counter-Narrative of Terrorism and Religion Violence in Islamic Boarding School - Ahsani Taqwim Aminuddin (Bappenas Working Papers, 2019)
This study aims to describe narrative texts held by Islamic boarding schools to fight terrorism or violence narratives and to describe activities carried out to support existing narrative texts. This study uses the Discourse Analysis method and divides the two stages of analysis. At the text analysis stage, the Islamic boarding school's narratives were analyzed using the Presidential Identity Prisma, while in the context analysis phase, the results of interviews and research observations were analyzed with Communication Performance to determine organizational culture and routine activities in Islamic Boarding Schools. The main theory used in this study is Fisher's Narrative Theory, which describes human decisions in believing in a narrative or story and acting on the belief in the story. According to Fisher, humans believe a narrative is influenced by the rationality of narratives, where the narrative has consistency and truth. The results of this study indicate that narrative texts have dominant Islamic boarding schools having coherence in the aspect of objectives that focus on the production of a message of peace so that Indonesia remains a country with a tolerant society and can manage existing differences. The figure of the Prophet Muhammad in the narrative is described as a person who prioritizes deliberation in solving problems. The Nahdlatul Ulama organization is also an organization that has the task of maintaining the unity of the people and nation of Indonesia in the midst of differences. Whereas, the efforts made to support narration are to routinely teach Islamic values as a religion of love in each forum; Reforming the education system; checking curriculum sourced from the government or from outside; Caregivers of Islamic boarding schools routinely form narratives to prevent terrorism, which are printed into books, sent to the media and so on so that the audience can easily access.